Appropriation réflexive des modalités d'usage du tableau noir par des enseignant(e)s en formation initiale - Gaëtan Temperman; Dominique Lucas; Bruno De Lièvre (Université de Provence, 2015)
In this contribution, we evaluate the impact of a formation aiming at helping of the pre-service teachers to adopt the use of the black board during their training courses. Starting the model of Kolb (1984), the mobilising idea of this formation is to lead the future teachers to adopt a reflexive behaviour, during and after the act to teach. For that purpose, this learning environment is articulated around a step face ton face between the first and the second training course as well as the step of sharing via the Internet during the second training course. Twenty-eight pre-service teachers in 2nd year of training in a high teaching school in the French Community of Belgium took part in this experimentation. To evaluate the effects, we twice analyse, on the one hand, the learning process perceived by the students and on the other hand, comments provided by the classroom teachers.